2020
DOI: 10.1002/pc.25716
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of surface‐pegylated nanocellulose as reinforcing agent on PBAT biodegradable nanocomposites

Abstract: In the present work, nanocellulose (NC) has been surface-pegylated and further employed as reinforcement in poly(butylene adipate-co-terephthalate) (PBAT) through the melting process. The nanocomposites showed a significant stiffness increase, especially the 2% pegylated-NC, due to the good interaction between the modified NC and the matrix. Also the pegylation improved the filler-PBAT adhesion, which resulted in higher thermal stability and low crystallinity. Raman spectroscopy confirmed the strong interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In Table 4, the CS/PBAT/PEG composite exhibits the highest activation energy, implying that it possesses the best thermostability. This result is consistent with that reported by Souza er al., 50 who found that PEG shows a positive influence on the thermostability of cellulose/ PBAT composite.…”
Section: Tga Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4, the CS/PBAT/PEG composite exhibits the highest activation energy, implying that it possesses the best thermostability. This result is consistent with that reported by Souza er al., 50 who found that PEG shows a positive influence on the thermostability of cellulose/ PBAT composite.…”
Section: Tga Measurementsmentioning
confidence: 99%
“…It means that PEG can promote the thermostability of CS/PBAT composite in a certain degree, which may be owing to the hydrogen bonds formed inside the composite that could restrict the movement of molecular chains, just as PEG did for the CG/PBAT composites. 27,49,50 The low T 1% value of CS/PBAT/GMA composite could be attributed to the slow volatilization of the remained unreacted GMA during the heating process.…”
Section: Tga Measurementsmentioning
confidence: 99%
“…It causes serious soil and marine pollution to threaten human health. [ 7–9 ] Biodegradable plastics, such as PLA, [ 10–14 ] PCL, [ 15–17 ] PBS, [ 18–20 ] and PBAT, [ 21,22 ] have been widely used in medical, agriculture, and packaging industries to replace non‐degradable materials to alleviate current environmental problems because they can be degraded to harmless substances such as H 2 O and CO 2 with the participation of microorganisms. [ 23–25 ]…”
Section: Introductionmentioning
confidence: 99%
“…such as PLA, [10][11][12][13][14] PCL, [15][16][17] PBS, [18][19][20] and PBAT, [21,22] have been widely used in medical, agriculture, and packaging industries to replace non-degradable materials to alleviate current environmental problems because they can be degraded to harmless substances such as H 2 O and CO 2 with the participation of microorganisms. [23][24][25] Among the biodegradable plastics, PBAT has attracted significant attention due to its good ductility, impact properties, and low processing temperature.…”
mentioning
confidence: 99%
“…In this context, polyethylene glycol (PEG) has been widely investigated as a compatibilizer in PBAT/cellulose based composites. Souza et al 25 reinforced PBAT with pegylated nanocellulose (pegylated-NC) by melt-mixing process. The nanocomposites presented improved mechanical properties attributed to good interaction and improved adhesion between pegylated-NC and the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%